Clinical Cysticercosis epidemiology in Spain based on the hospital discharge database: What's new? - Zaida Herrador; Amalia Fernandez-Martinez; Agustín Benito; Rogelio Lopez-Velez (Public Library of Science (PLoS), 2018)
Cysticercosis (CC) is a tissue infection caused by the larval cysts of the pork tapeworm Taenia solium. It is usually acquired by eating contaminated food or drinking water. CC Cysts can develop in the muscles, the eyes, the brain, and/or the spinal cord. T. solium is found worldwide, but its prevalence has decreased in developed countries due to stricter meat inspection and better hygiene and sanitation. Nevertheless, CC is still a leading cause of seizures and epilepsy. In Spain, The disease is not nationally reportable and data on CC infected animals are also missing, despite the European Directive 2003/99/EC.We performed a retrospective descriptive study using the Spanish Hospitalization Minimum Data Set (CMBD). Data with ICD-9 CM cysticercosis code ("123.1") placed in first or second diagnostic position from 1997 to 2014 were analyzed. Hospitalization rates were calculated and clinical characteristics were described. Spatial distribution of cases and their temporal behavior were also assessed. A total of 1,912 hospital discharges with clinical cysticercosis were identified. From 1998 to 2008, an increasing trend in the number of CC hospitalizations was observed, decreasing afterwards, in parallel with a decrease in the external migration rate. The Murcia region had the highest median hospitalization rate (13.37 hospitalizations/100,000 population), followed by Navarra and Madrid. The 16-44 age group was the most represented (63.6%). The three most frequent associated diagnoses were epilepsy and convulsions (49.5%), hydrocephalus (11.8%) and encephalitis/myelitis/meningitis (11.6%).There is a need for a common strategy on data collection, monitoring and reporting, which would facilitate a more accurate picture on the CC epidemiological scenario. Even if most cases might be imported, improving the human and animal CC surveillance will result useful both in gaining extended disease knowledge and reducing morbidity and related-costs.